Pengembangan Prasarana Irigasi untuk Peningkatan Produktivitas Lahan di Kabupaten Konawe, Sulawesi Tenggara - Purwanto, M Yanuar J; Subari, -; Nur, Friday Fritriana (Balai Teknik Irigasi, 2013)
In the agricultural land with low productivity will also produce less gross domestic income, and also have low income per capita in the region. In this case, productivity of land should be increased. The land productivity is as coefficient value calculated by total revenue comes from any cropping pattern and other added value product from raw materials harvested in the region. To understand the land produtivity needs the relationship between the total revenue and total area of the harvested cropping pattern in the revenue region. The objective of study was to develop an analysis model as a strategy for infrastructure development by improving the quality of irrigation infrastructure. The irrigation infrastructure were planned come from simple to the technical irrigation system by considering to the adequacy of available water, food security and welfare. The study was done in the Irrigation System of Wawotobi and the result shows that the plan of irrigation development for achieving the necessary food self-sufficiency and higher income can be succesfully reached along with a revenue model in 2020 chracterised by level of implemented scenarioes of added values in the region.